ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN KREDIT TERHADAP PENGENDALIAN INTERNAL PADA PT. ACE HARDWARE INDONESIA TBK TAHUN 2019 - Sutrisno Sutrisno; Abdul Majied (JURNAL LENTERA AKUNTANSI, 2020)
The Writer take has choosen the theme that has named Installment Sales Accounting System Analysis of Internal Control at ACE Hardware Indonesia Inc. at 2019 to describing about the different implementation of Installment Sales Accounting System Analysis and Internal Control at ACE Hardware Indonesia Inc. between the Mulyadi’s Theory. This obeservation is a qualitative observation with the descriptive methods, It’s included with the observation from January till December,2019. the sources of information based on documentation and interviewing the respondens which work on that activity as the primary datas meanwhile Documents and Attachments as secondary datas. The result of the observation: there’s have dissonant the implementation. It shown with the disproportionate jobdesk of each other, the writer could suggest to increase the quality of facilities and increase the human resources of the company. Keywords: Installment Sales Accounting Information System, Internal Control